Melanocytic Lesions With Peripheral Globules: Proposal Of An Integrated Management Algorithm - Cappilli, Simone; Ribero, Simone; Cornacchia, Luigi; Catapano, Silvia; Del Regno, Laura; Quattrini, Laura; D'Amore, Alessandra; Federico, Francesco; Broganelli, Paolo; Peris, Ketty; Di Stefani, Alessandro (Dermatology practical & conceptual, 2023)
Introduction: A peripheral rim of globules represents a marker of horizontal growth phase in nevi and is a common feature in  children and adolescents. The observation of melanocytic lesion with peripheral globules (MLPG) in adulthood deserve more attention, since a melanoma may exhibits this feature albeit rarely. Risk stratified management recommendations considering a global clinical approach are still missing. Objectives: To analyze current knowledge on MLPG and propose an integrated management algorithm stratified for age groups. Methods: We conducted a narrative review of current published data on MPLG, analyzing clinical dermoscopic and confocal distinguishing features of melanoma from bening nevi. Results: The risk of finding a melanoma when removing a MLPG increases with age especially in people >55 years old and results significantly higher on extremities, head/neck and in case of a single asymmetrical lesion, ≥6 mm in diameter. Dermoscopic features associated to melanoma diagnosis include atypical peripheral globules, asymmetrical distribution,  multiple rims as well as globules reappearance after previous loss. In addition, wide blue-grey regression areas, atypical network, eccentric blotches, tan structureless peripheral areas and vascularizationare atypical dermoscopic features. Confocal worrisome findingss are represented by pagetoid cells within the epidermis, architectural disarrangement and atypical cells of the dermo-epidermal junction with irregular peripheral nests. Conclusion: We proposed a multi-step age-stratified management algorithm integrating clinical, dermoscopic and confocal findings that may increase the early recognition of melanoma and avoid surgical excision of benign nevi.